The prognostic impact of the extent of ulceration in patients with clinical stage I–II melanoma: a multicentre study of the Italian Melanoma Intergroup (IMI). (1st February 2021) - Portelli, F.; Galli, F.; Cattaneo, L.; Cossa, M.; De Giorgi, V.; Forte, G.; Fraternali Orcioni, G.; Gianatti, A.; Indini, A.; Labianca, A.; Maurichi, A.; Merelli, B.; et al.
Summary: Background: The presence of ulceration has been recognized as an adverse prognostic factor in primary cutaneous melanoma (PCM). Objectives: To investigate whether the extent of ulceration (EoU) predicts relapse‐free survival (RFS) and overall survival (OS) in PCM. Materials and methods: We retrieved data for 477 patients with ulcerated PCM from databases of the Italian Melanoma Intergroup. Univariate and multivariable Cox proportional hazard models were used to assess the independent prognostic impact of EoU. Results: A significant interaction emerged between Breslow thickness (BT) and EoU, considering both RFS ( P < 0·0001) and OS ( P = 0·0006). At multivariable analysis, a significant negative impact of EoU on RFS [hazard ratio (HR) (1‐mm increase) 1·26, 95% confidence interval (CI) 1·08–1·48, P = 0·0047] and OS [HR (1‐mm increase) 1·25, 95% CI 1·05–1·48, P = 0·0120] was found in patients with BT ≤ 2 mm, after adjusting for BT, age, tumour‐infiltrating lymphocytes, sentinel lymph node status and mitotic rate. No impact of EoU was found in patients with 2·01–4 mm and > 4 mm BT. Conclusions: This study demonstrates that EoU has an independent prognostic impact in PCM and should be recorded as a required element in pathology reports.